The ethics of policing: new perspectives on law enforcement - Jones, Ben; Mendieta, Eduardo (New York University Press, 2021)
"This book offers a wide-ranging analysis of the current ethical challenges facing police and the institutions that oversee them, featuring contributions from leading experts in black studies, criminology, history, law, philosophy, political science, and sociology"--